2017
DOI: 10.1002/chem.201605952
|View full text |Cite
|
Sign up to set email alerts
|

Chemisorption of a Strained but Flexible Molecule: Cyclooctyne on Si(001)

Abstract: What aspects of this project do you find most exciting? The application of bonding analysis methods from molecular chemistry to extended systems (surfaces, solids) provides an important insight into the driving forces of surface chemistry.F or arather large molecule as cyclooctyne, these methods allow to distinguish which effects are caused by the functional group, the molecular ring strain, and the sheer size of the molecule. Furthermore, the well-known failure of many DFT functionals in describing dis-persiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 26 publications
(88 citation statements)
references
References 53 publications
6
82
0
Order By: Relevance
“…The dispersion interaction term is computed from the prepared fragments to be consistent with the other energy terms in the pEDA. It thus deviates from the usual dispersion interaction term computed via the supermolecular approach . The actual EDA procedure then decomposes Δ E int (elec) into contributions from Pauli repulsion, electrostatics (elstat) and orbital interaction (orb): ΔEint()elec=ΔEPauli+ΔEelstat+ΔEorb0.25em …”
Section: Methodsmentioning
confidence: 96%
“…The dispersion interaction term is computed from the prepared fragments to be consistent with the other energy terms in the pEDA. It thus deviates from the usual dispersion interaction term computed via the supermolecular approach . The actual EDA procedure then decomposes Δ E int (elec) into contributions from Pauli repulsion, electrostatics (elstat) and orbital interaction (orb): ΔEint()elec=ΔEPauli+ΔEelstat+ΔEorb0.25em …”
Section: Methodsmentioning
confidence: 96%
“…An alternative idea would be to assume that the reaction is under thermodynamic control. This also does not deliver a coherent picture, since all theoretical studies predict the on-top mode to be more stable than bridge at low coverage [20,21,30,35,57]. Therefore, a new, presumably more complex model of the adsorption dynamics must be devised, which we cannot provide at this moment.…”
Section: Comparison With Experimentsmentioning
confidence: 92%
“…In the c direction, a vacuum layer of at least 10 Å was ensured. Convergence studies on these parameters can be found in a previous work [57]. The bonding energy E bond was defined as the difference between the energy E tot of the relaxed total system and the energies E surf and E mol of the relaxed and isolated surface and molecule:…”
Section: Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] As one of the few examples, Tonner and co-workers have demonstrated that EDAs on semi-conducting surfaces can provide a deep understanding of coverage effects 12 and elucidate peculiar bonding mechanisms. 13 Our goal is to extend the EDA based on the block-localized wave function (BLW) 14,15 to metallic surfaces. The BLW is designed to localize the electrons in Hilbert space in the Mulliken sense, i.e., in terms of atom-centered basis functions.…”
Section: Introductionmentioning
confidence: 99%